Self-regulation of learning and performance level of elite youth soccer players - Toering, T.; Elferink-Gemser, M. T.; Jordet, G.; Pepping, G. J.; Visscher, C. (International Journal of Sport Psychology, 2012)
This study examined the relationship between self-regulated learning and performance level of 256 elite youth soccer players aged 12 to 17 years (Mage = 14.2; SD = 1.2). As relative age may affect this relationship through its association with maturation, experience, and performance level, we controlled for relative age. Practice and match experience was equal across groups [international (n = 76) vs. national level (n = 178)]. A logistic regression analysis revealed that players scoring high on reflection and players born in the first half of a selection year were more likely to belong to the international group (OR = 1.69 and 2.18, respectively). Relative age did not affect the relationship between reflection and performance level. We suggest that international players benefit more from practice than national players through reflective thinking. Additionally, given international players` higher reflection scores irrespective of relative age, reflection may be a cognitive-behavioral marker of talent.